2022
DOI: 10.4102/sajhrm.v20i0.1909
|View full text |Cite
|
Sign up to set email alerts
|

Workplace bullying in a South African higher education institution: Academic and support staff experiences

Abstract: Workplace bullying is a common occurrence in organisations worldwide, and higher education institutions are no exception.Research purpose: This study was conducted with the aim of determining the perceptions of workplace bullying amongst academic and support staff at a higher education institution in South Africa and to ascertain how they are affected by selected sociodemographic variables.Motivation for the study: Currently, there are limited published research studies reporting on the prevalence and/or exper… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(13 citation statements)
references
References 47 publications
0
13
0
Order By: Relevance
“…The foci of the included Figure 2 Frequency distribution of the year of publication of reviewed articles studies were varied. Six of the studies focused on different things that could contribute to or shape the bullying experience, such as gender, group identification or psychosocial factors (Anjum and Muazzam, 2018;Badenhorst and Botha, 2022;Bjo ¨rklund et al, 2021;Glambek et al, 2020;Goodboy et al, 2022;Hodgins and McNamara, 2017). Five of the studies looked into effects of bullying on various factors (e.g.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…The foci of the included Figure 2 Frequency distribution of the year of publication of reviewed articles studies were varied. Six of the studies focused on different things that could contribute to or shape the bullying experience, such as gender, group identification or psychosocial factors (Anjum and Muazzam, 2018;Badenhorst and Botha, 2022;Bjo ¨rklund et al, 2021;Glambek et al, 2020;Goodboy et al, 2022;Hodgins and McNamara, 2017). Five of the studies looked into effects of bullying on various factors (e.g.…”
Section: Resultsmentioning
confidence: 99%
“…Authors made use of questionnaires ( n = 13), interviews ( n = 4) and content analysis ( n = 1). Not every study used a previously developed and validated measure, though 11 did (Anjum and Muazzam, 2018; Anjum and Muazzam, 2019; Anjum et al , 2019; Badenhorst and Botha, 2022; Björklund et al , 2021; Coyne et al , 2017; Erkutlu and Chafra, 2014; Giorgi, 2012; Glambek et al , 2020; Goodboy et al , 2022; Malik and Björkqvist, 2019). The most frequently used measure was the Negative Acts Questionnaire – Revised (Badenhorst and Botha, 2022; Coyne et al , 2017; Erkutlu and Chafra, 2014; Giorgi, 2012; Glambek et al , 2020; Goodboy et al , 2022).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Giovaziolas & Malikiosi-Loizos, 2016;Kokkinos et al, 2016;Spanou et al, 2020) have shown a strong interest in the topic. Other countries where bullying in higher education has been the subject of research include China (Su et al, 2022;Zhao et al, 2022), India (Kaur & Kaur, 2023;Sinha & Bondestam, 2022), Pakistan (Ahmed et al, 2022), South Africa (Badenhorst & Botha, 2022), Spain (Yubero et al, 2023), Turkey (Akbulut & Eristi, 2011) and the United Arab Emirates (Al-Damarki et al, 2022).…”
Section: Methodsmentioning
confidence: 99%